New Trends in Corpora and Language Learning - Flowerdew, Lynne,Aston, Guy,Frankenberg-Garcia, Ana (Bloomsbury Publishing Plc, 2012)
This book provides an up-to-date snapshot of recent research and developments in the use of corpora for language learning and teaching. It is divided into three parts. Part I focusses on innovative uses of corpora by language teachers and learners. These cover the world's first corpus-based TV program for the teaching of English conversation, as well as corpus-based approaches to the teaching of EAP, cultural studies and translation. Part II focuses on new corpus-based tools for LSP learning. Part III illustrates research findings from corpora consisting of language learner data and discusses their implications for language teaching and learning. It will appeal to scholars in both language teaching and learning and corpus and computational linguistics.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Korpus; Fremdsprachenlernen; Computerunterstütztes Lernen